Warmer Ambient Temperatures Depress Detoxification and Food Intake by Marsupial Folivores - Beale, Phillipa K.; Connors, Patrice K.; Dearing, M. Denise; Moore, Ben D.; Krockenberger, Andrew K.; Foley, William J.; Marsh, Karen J. (Frontiers in Ecology and Evolution, 2022)
Ambient temperature is an underappreciated determinant of foraging behaviour in wild endotherms, and the requirement to thermoregulate likely influences food intake through multiple interacting mechanisms. We investigated relationships between ambient temperature and hepatic detoxification capacity in two herbivorous marsupials, the common ringtail possum (Pseudocheirus peregrinus) and common brushtail possum (Trichosurus vulpecula) that regularly feed on diets rich in plant toxins. As an indicator of hepatic detoxification capacity, we determined the functional clearance rate of an anaesthetic agent, Alfaxalone, after possums were acclimated to 10°C (below the thermoneutral zone), 18°C (approximately lower critical temperature), and 26°C (approximately upper critical temperature) for either seven days or less than 24 h. We then measured intake of foods with high or low plant secondary metabolite concentrations under the same temperature regimes. After seven days of acclimation, we found a positive correlation between the functional clearance rate of Alfaxalone and ambient temperature, and a negative relationship between ambient temperature and intake of foods with high or low plant secondary metabolite concentrations for both species. The effect of ambient temperature on intake of diets rich in plant secondary metabolites was absent or reduced when possums were kept at temperatures for less than 24 h. Our results underscore the effects of ambient temperature in hepatic metabolism particularly with respect intake of diets containing plant secondary metabolites. Given that the planet is warming, it is vital that effects of ambient temperature on metabolism, nutrition and foraging by mammalian herbivores is taken into account to predict range changes of species and their impact on ecosystems.